Analysis of the effect of injuries on match performance variables in professional soccer players: A retrospective, experimental longitudinal design - Raya-González, J.; Pulido, J. J.; Beato, M.; Ponce-Bordón, J. C.; del Campo, R. L.; Resta, R.; García-Calvo, T. (Sports Medicine - Open, 2022)
Background Knowing the impact of injuries is essential for their adequate management during reconditioning programs.